Lung function changes over time following withdrawal of inhaled corticosteroids in patients with severe COPD. Issue 2 (19th November 2015) - Magnussen, Helgo; Tetzlaff, Kay; Bateman, Eric D.; Watz, Henrik; Kirsten, Anne M.; Wouters, Emiel F.M.; Disse, Bernd; Finnigan, Helen; Rodriguez-Roisin, Roberto; Calverley, Peter M.A.
The combination of an inhaled long-acting β2 -agonist with an inhaled corticosteroid (ICS) is widely used in the management of chronic obstructive pulmonary disease (COPD), primarily to prevent exacerbations [1]. Concerns about the increased risk of pneumonia, even with newer ICS [2], have generated interest in whether the ICS can be safely withdrawn from patients with COPD. We recently reported, in the WISDOM (Withdrawal of inhaled steroids during optimized bronchodilator management) study (clinicaltrials.gov identifier number: NCT00975195), that patients who continued treatment with a long-acting β2 -agonist plus a long-acting muscarinic antagonist did not have an increased risk of exacerbations [3]. However, we observed a statistically significant difference in forced expiratory volume in 1 s (FEV1 ) after complete ICS withdrawal and at the end of the study in favour of continued ICS treatment. Decreased FEV1 after complete ICS withdrawal in severe COPD was not progressive and did not predict clinical changes http://ow.ly/TtYDV